Crystal structure of a novel myotoxic Arg49 phospholipase A(2) homolog (zhaoermiatoxin) from Zhaoermia mangshanensis snake venom: Insights into Arg49 coordination and the role of Lys122 in the polarization of the C-terminus - Murakami, Mario T. [UNESP]; Kuch, Ulrich; Betzel, Christian; Mebs, Dietrich; Arni, Raghuvir K. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The venom of Zhaoermia mangshanensis, encountered solely in Mt Mang in China's Hunan Province, exhibits coagulant, phosphodiesterase, L-amino acid oxidase, kallikrein, phospholipase A(2) and myotoxic activities. The catalytically inactive PLA(2) homolog referred to as zhaoermiatoxin is highly myotoxic and displays high myonecrotic and edema activities. Zhaoermiatoxin possesses a molecular weight of 13,972 Da, consists of 121 amino-acid residues crosslinked by seven disulfide bridges and shares high sequence homology with Lys49-PLA(2)s from the distantly related Asian pitvipers. However, zhaoermiatoxin possesses an arginine residue at position 49 instead of a lysine, thereby suggesting a secondary Lys49 -> Arg substitution which results in a catalytically inactive protein. We have determined the first crystal structure of zhaoermiatoxin, an Arg49-PLA(2), from Zhaoermia mangshanensis venom at 2.05 A resolution, which represents a novel member of phospholipase A(2) family. In this structure, unlike the Lys49 PLA(2)s, the C-terminus is well ordered and an unexpected non-polarized state of the putative calcium-binding loop due to the flip of Lys122 towards the bulk solvent is observed. The orientation of the Arg-49 side chain results in a similar binding mode to that observed in the Lys49 PLA(2)s; however, the guadinidium group is tri-coordinated by carbonyl oxygen atoms of the putative calcium-binding loop, whereas the N zeta atom of lysine is tetra-coordinated as a result of the different conformation adopted by the putative calcium-binding loop. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Zhaoermia mangshanensis; Snake venom; Arg49-phospholipase A(2); Lys49-phospholipase A(2); myotoxin; Crystal structure